(untitled) (Ukrainian Journal of Ophthalmology, 2025)
The article focuses on the results of diagnostic studies and research performed in the Ophthalmic Pathomorphology Laboratory over the 75 years of its existence. More than 250,000 histological studies of surgical clinical material and biopsy material from more than 100,000 patients have been performed over the whole period of existence of the laboratory since 1946. In addition, about 1000 science works including 26 monographs have been published, and dozens of ophthalmologists were provided special assistance in performing morphological studies for their doctoral dissertations and candidate of science theses.